Surface Modification of Smectite Clay Induced by Non-thermal Gliding Arc Plasma at Atmospheric Pressure - Djowe, Antoine Tiya; Laminsi, Samuel; Njopwouo, Daniel; Acayanka, Elie; Gaigneaux, Eric M. (Plasma chemistry and plasma processing, 2013)
Smectite clay from Sabga (west-Cameroon) was treated in aqueous suspension by gliding arc plasma to modify its surface properties. The evolution of the modifications was followed with the exposure time and post-discharge duration using Fourier transformed infra red spectroscopy and scanning electron microscopy. X-ray diffraction and nitrogen physisorption analyses were also performed to evaluate if both crystalline and textural properties of the material are affected by the treatment. The results obtained show that the plasma treatment causes the breakdown of structural bounds at the clay surface and induces the formation of new hydroxyl groups (Si–OH and Al–OH) on the clay edges. Crystallinity, sheet structure and textural properties are not significantly affected by the plasma treatment. However, it should be noted that an intensive treatment of the clay lowers the pH of the suspension, which subsequently induces an acid attack of the clay. In such case, the specific surface area of the clay increases. This study demonstrates that gliding arc plasma treatments can be used to activate clay minerals for environmental application.